1995
DOI: 10.1055/s-2008-1066154
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Children with Diaphragmatic Hernia

Abstract: From 1962 to 1988, 147 neonates were admitted for operative repair of CDH to the Division of Pediatric Surgery in the Children's Hospital of Cologne. Follow-up studies were performed on 45 patients ages 1 to 25 years representing 54.2% of the 83 survivors. 18 patients (40%) were entirely without any complaints, 11 patients (24.4%) had increased rates of respiratory infections. Especially in early childhood they suffered from obstructive alterations in the respiratory tract. No restrictive pulmonary changes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 2 publications
3
25
1
1
Order By: Relevance
“…In the study from Marven et al [66], CDH patients perceived their own fitness to be worse than the healthy control group. Other studies demonstrate that around 20% of interviewed CDH patients consider themselves less fit than their healthy peers [59,65,73]. It seems most likely that the decreased V 0 O 2 max found by Zaccara et al is due to a lower degree of physical fitness.…”
Section: Pulmonary Functionmentioning
confidence: 88%
See 4 more Smart Citations
“…In the study from Marven et al [66], CDH patients perceived their own fitness to be worse than the healthy control group. Other studies demonstrate that around 20% of interviewed CDH patients consider themselves less fit than their healthy peers [59,65,73]. It seems most likely that the decreased V 0 O 2 max found by Zaccara et al is due to a lower degree of physical fitness.…”
Section: Pulmonary Functionmentioning
confidence: 88%
“…FEV1 and/or FEV1/FVC are decreased in patients with airway obstruction. Wischerman et al [59] reported normal FEV 1 in CDH patients, but found a tendency to obstruction of the smaller airways illustrated by reduction in the mid-expiratory flow rate and raised specific airway resistance. There was no correlation between the extent of pulmonary hypoplasia, assessed during the operation and by pre-and postoperative chest Xrays, and reduction of airflow rate [59].…”
Section: Pulmonary Functionmentioning
confidence: 99%
See 3 more Smart Citations